Faktor-Faktor Yang Berhubungan Dengan Pemberian ASI Eksklusif Pada Ibu Bekerja Di Klinik Sehati Medan Tahun 2023 - Yuniria Tafonao; Basaria Manurung (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Breast milk (ASI) is the best food for newborn babies and is the only healthy food that babies need in the first months of life. However, not all mothers can provide exclusive breast milk to their babies. This research aims to determine the factors associated with providing exclusive breast milk to working mothers at the Sehati Medan Clinic in 2023. This type of research is research using an analytical survey with a cross sectional method approach. The population is all mothers who have babies 0-6 months at the Sehati Medan Clinic, totaling 38 people. The number of samples used was 38 people obtained using the total sampling technique. The data analysis technique uses chi square. The results obtained in this study were that from 38 respondents, there was a relationship between the education of breastfeeding mothers and exclusive breastfeeding for babies 0-6 months old, showing that the p value = 0.014 < 0.05, there was a relationship between the age of breastfeeding mothers and exclusive breastfeeding for babies. 0-6 Months shows that the p value = 0.001 < 0.05, , there is a relationship between the Type of Work of Breastfeeding Mothers and Exclusive Breastfeeding for Babies 0-6 Months shows that the value of p = 0.000 < 0.05, there is a relationship between the Mother's Length of Work Breastfeeding with Exclusive Breastfeeding for Babies 0-6 Months shows that the p value = 0.023 < 0.05. It is recommended for Health Workers to increase education regarding Exclusive Breastfeeding.